Sensitivitas Fosfomycin pada ISK Akibat Infeksi Enterobacteriaceae Penghasil ESBL pada Pasien di RS X Tahun 2023 - William Dharma Wijaya; Layanto, Nicolas; Dharmawan, Ade (Universitas Kristen Krida Wacana, 2025)
Urinary tract infection (UTI) is one of the most common infections in humans. However, intensive and extensive use and misuse of antibiotics over the past 50 years such as in the use of carbapenems, resistance to antibiotics increased dramatically in recent years, especially in Enterobacteriaceae. This study aims to determine the sensitivity of fosfomycin as an drug option in treating UTI due to Extended-spectrum-β-Lactamase (ESBL)-producing Enterobacteriaceae in the era of increasing antibiotic resistance. This study is an analytical descriptive study with a cross-sectional observational design, by looking at the sensitivity pattern of ESBL-producing Enterobacteriaceae causing UTI at a certain point in time. This study used secondary data in the form of microbiology laboratory results at Hospital X in 2023. The results showed that ESBL-producing Enterobacteriaceae causing urinary tract infections were dominantly found Escherichia coli (79.41%). The level of fosfomycin sensitivity to non-ESBL-producing and ESBL-producing Enterobacteriaceae is very good and there are no significant differences in the results of the use of fosfomycin in urinary tract infections due to non-ESBL-producing and ESBL-producing Enterobacteriaceae, with the percentage being (91.31%) and (91.17%). Thus fosfomycin can be a drug option in treating UTI due to ESBL-producing Enterobacteriaceae infection.